Dinosaurs and other vertebrates from the Papo-Seco Formation (Lower Cretaceous) of southern Portugal - Figueiredo, S. D.; Rosina, P.; Figuti, L. (Journal of Iberian Geology, 2015)
New vertebrate remains reported from the Papo-Seco Formation (Lower Barremian, Lower Cretaceous) of Areias do Mastro, in Cabo Espichel, SW Portugal, south of Lisbon. The marine, lagoonal, and estuarine limestones, marls, sands and gravels have yielded remains of dinosaurs and other reptiles since the 19th century. Recent paleontological prospecting produced several vertebrate remains, including turtle shell fragments, crocodilian teeth, fish and pterosaurs. Research identified both bones and teeth of fish, crocodiles, dinosaurs Baryonyx and iguanodontian, as well as a ctenochasmatoid pterosaur, and a possible ornithocheirid pterosaur. These new disclosures are an important contribution to the knowledge of vertebrate diversity from the Portuguese Cretaceous. Faunal species combination proven to be similar to other faunal associations of Barremian formations in the Iberian Peninsula.